SIMULATIONAL AND EXPERIMENTAL STUDY ON THE CRITICAL FACTORS OF HIGH-SPEED BRAKING SQUEAL - ZHANG ErYin; WANG ShuWen; SUN YueDong; WEI Jian; CHEN Kang (Jixie qiangdu)
Complex eigenvalue analysis using ABAQUS has been carried out,based on a simplified finite element model of high-speed disc brake system.The critical factors generating brake squeal have been computationally studied and verified by experiments.Simulation results show that,brake squeal more likely to occur under the conditions of low-speed,high pressure,negative μ-υ slope,and high coefficient of friction.The effects of sliding speed and normal contact pressure on the generation of brake squeal have been verified.This study will provide effective guidance in the prevention and control of brake squeal.